A Study of Student Non-Attendance Based on Cultural Commitments, Generational Change, and the Impact of Artificial Intelligence and Social Life Online: An Analytical Study Among Students of Saudi Universities - Almakky, Hana Ghazy (Journal of Cultural Analysis and Social Change, 2026)
Across Saudi universities, attendance rates among undergraduates have been quietly trending downward for several years — but the explanations provided by institutional reports rarely stray far from descriptive accounts based on student disengagement or poor planning. This study adopts a different perspective. Rather than asking why students don't make it to class, we asked what they're actually deciding when they don't come in, and found a picture much more complex than the policy discourse is often prepared to recognize. Drawing on a convergent mixed-methods approach, we gathered questionnaire data from 87 undergraduates enrolled in three public Saudi universities and conducted 45- to 75-minute semi-structured interviews with 15 students selected for diversity by gender, discipline, and attendance pattern. Multiple regression analysis identified AI reliance (β = .35, p < .001), perceived learner independence (β = .32, p < .001), and social media engagement (β = .27, p = .009) as the dominant predictors of absenteeism, collectively accounting for 48% of variance (R² = .48). Mediation analysis (PROCESS Model 4; 5,000 bootstraps) confirmed that AI reliance exerts part of its effect indirectly — by amplifying students' sense of learning independence — which in turn drives higher absence rates. The interview data complicate any simple technological-determinism reading of these numbers. Students draw explicit distinctions between lecture formats they consider substitutable and interactive sessions they regard as irreplaceable. Family obligations — disproportionately carried by women — explain a further share of absences that have nothing to do with motivation. And a recurring theme across almost every interview was a direct challenge to institutional authority: attendance mandates that cannot be pedagogically justified provoke skepticism rather than compliance. Taken together, the findings suggest that attendance policy in Saudi higher education needs to be rebuilt around the actual conditions shaping student decisions rather than assumptions calibrated to an earlier technological era.